Respons Peningkatan Nutrisi Pelepah Sawit Fermentasi yang Diinokulasi dengan Inokulum Berbeda - Danang Biyatmoko (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
The purpose of this study was to determine the effect of different types of inoculum for protein content ( PK ) and crude fiber fermentation of palm frond. Research using randomized design (RAL) 4 treatments and 5 replications . Treatment studies are differences in the type of inoculum fermentation, covering S0 ( control ) , S1 ( EM - 4 ) , S2 ( Trichoderma viridae ) and S3 (Sacharomyces cerevisiae). The variables measured were protein content ( PK ) and crude fiber (SK) from the fermentation of palm frond. Results this research it can be concluded that fermentation using palm frond types of different inoculum showed increased protein results (PK) significantly fermented palm frond of 2,11 % ( control ) to 2,41 ( inoculum EM - 4 ) , while the fiber content ( SK ) not significantly different but showed a declining trend with the use of inoculum in the fermentation of palm frond . Best inoculum recommendations to improve the nutritional value of fermented palm frond is effective microorganism ( EM - 4 ) .